Factors affecting the purchase of green products among the selected millennials in Melaka / Puteri Aliah Athirah Megat Nor Mazlan - Megat Nor Mazlan, Puteri Aliah Athirah (Faculty of Business and Management, 2019)
Green purchasing have become an interesting topic to be debate especially among young generation. The attempt of this research is to study the factors affecting the purchase of green products among the selected millennial in Melaka. This research are aiming to study about the relationship between dependent variable which is green purchasing and independent variable which are social influence, perceived environmental knowledge, eco-labelling, and exposure to environmental messages through the media. This research is distributed in Melaka, specifically at the University Technology MARA Bandaraya Melaka, Melaka Sentral Bus Terminal, Tesco Mall Bandaraya Melaka, Aeon Mall Bandaraya Melaka, Mahkota Parade and Dataran Pahlawan area. A set of 384 questionnaires are distributed among students, staffs, and public person who are willingly to contribute in this study. Out of 384 data collected, only 259 data are analyse in this study using Descriptive Analysis, Reliability Analysis, Correlation Analysis and Multiple Regression Analysis. The analysis is conducted using SPSS software version 25. The result of the study are expected to be that there is a relationship between dependent variables and independent variables of the study.